IMPROVING STUDENTS’ SPEAKING SKILL BY USING PICTURE STRIP STORY - Odi Kosdian (Indonesian EFL Journal, 2016)
This research is aimed at improving students’ speaking skill by using picture strip story in class XI IPA 1 of Senior High School 1 Luragung. The problems in this research are the low of students’ skill in speaking. This research was applied through collaborative action research which was conducted in two cycles. The subject of this research was English subject in class XI IPA I with total number of students 34. The result of the research showed that picture strip story could improve students’ speaking skill. The result of test I was 62.69, test II was 68.83 and test III was 74.22. The students who passed the Minimum Mastery Criterion (KKM) were 22 students or 64.71%. In addition, the result of field notes showed that the classroom situation during teaching learning process by using picture strip story created the positive atmosphere. In cycle 1, there were no students who chatted and played handphone during the teaching and learning process by using picture strip story, all of students in a group did the task together and discussed it each other, the students could answer teacher’s question, and all of students spoke in English while expressing their ideas. In cycle 2, the classroom situations were completed with students asking questions to the teacher.Keywords: speaking skill, picture strip story, improve, collaborative action research